2001
DOI: 10.1159/000050633
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Carcinoembryonic Antigen, CA 19-9 and CA 72-4 in Gastric Carcinoma

Abstract: The prognostic value of preoperative serum levels of carcinoembryonic antigen (CEA), CA 19-9 and CA 72-4 tumor markers was investigated in patients with gastric cancer. Eighty-two patients who underwent surgical resection of gastric cancer were entered in the study. Correlation analyses showed that CA 72-4 was more frequently positive in patients with advanced tumors (p = 0.04), lymph node invasion (p = 0.02), liver metastasis (p = 0.02) and peritoneal involvement (p = 0.03). CA 19-9 was more frequently positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 16 publications
5
79
2
2
Order By: Relevance
“…Several studies have demonstrated CEA to have independent prognostic value, 5,17-21 but in other studies no significant correlation with survival has been found. 6,7,13,22,23 CA 19-9 has also been shown to be an independent prognostic factor in some 5,19,22 but not in other studies. 6,7,13,21,23 Furthermore, CA 72-4 has been reported to be a stronger prognostic factor than CEA and CA 19-9 in gastric cancer 6 but in other studies CA 72-4 has lacked independent prognostic value.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Several studies have demonstrated CEA to have independent prognostic value, 5,17-21 but in other studies no significant correlation with survival has been found. 6,7,13,22,23 CA 19-9 has also been shown to be an independent prognostic factor in some 5,19,22 but not in other studies. 6,7,13,21,23 Furthermore, CA 72-4 has been reported to be a stronger prognostic factor than CEA and CA 19-9 in gastric cancer 6 but in other studies CA 72-4 has lacked independent prognostic value.…”
Section: Discussionmentioning
confidence: 79%
“…6,7,13,22,23 CA 19-9 has also been shown to be an independent prognostic factor in some 5,19,22 but not in other studies. 6,7,13,21,23 Furthermore, CA 72-4 has been reported to be a stronger prognostic factor than CEA and CA 19-9 in gastric cancer 6 but in other studies CA 72-4 has lacked independent prognostic value. 5,7 Of the less-established tumour markers in gastric cancer, we have previously shown CA 242 to be an independent prognostic factor in colorectal cancer, 9 but to the best of our knowledge, the association between CA 242 and survival has not been reported in gastric cancer.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Although the positive rates for CEA, CA19-9, and CA72-4 were similar in detecting major tumors, CA72-4 had the highest positive rate in patients with nodal involvement or serosal invasion. Therefore, CA72-4 was the most useful marker for detecting advanced gastric cancer [34,39,42,43].…”
Section: Manuscript Selectionmentioning
confidence: 99%
“…CEA was strongly associated with the T factor [29,30,33,37], [11] analyzed 68 patients with stage IV gastric cancer using multivariate analysis and concluded that an elevated CEA level was an independent risk factor for predicting liver metastases. A few reports have shown a significant association between elevated CEA and peritoneal metastases [18,34]. Although several reports showed that elevated CEA was significantly associated with differentiated tumor types [7,10,48,61], a few reports indicated an association with poorly differentiated types of tumors [29].…”
Section: Ceamentioning
confidence: 99%